Nomogram predicts CR-POPF in open central pancreatectomy patients with benign or low-grade malignant pancreatic neoplasms - Ouyang, Liu; Liu, Ren-dong; Ren, Yi-wei; Nie, Gang; He, Tian-lin; Li, Gang; Zhou, Ying-qi; Huang, Zhi-ping; Zhang, Yi-jie; Hu, Xian-gui; Jin, Gang (Frontiers in Oncology, 2022)
Introduction Central pancreatectomy (CP) is a standard surgical procedure for benign and low-grade malignant pancreatic neoplasms in the body and neck of the pancreas. Higher incidence of clinically relevant postoperative pancreatic fistula (CR-POPF) after CP than after pancreaticoduodenectomy (PD) or distal pancreatectomy (DP) has been reported, but no nomogram for prediction of CR-POPF after open CP has been previously established. Methods Patients undergoing open CP for benign or low-grade malignant pancreatic neoplasms in the department of Hepatobiliary and Pancreatic (HBP) surgery of Shanghai Changhai Hospital affiliated to Naval Medical University between January 01, 2009 and December 31,2020 were enrolled. Pre-, intra- and post-operative parameters were analyzed retrospectively. Results A total of 194 patients, including 60 men and 134 women, were enrolled with median age of 52 years (21~85 years). 84 patients (43.3%) were overweight (BMI>23.0 Kg/m2) and 14 (7.2%) were obese (BMI>28.0 Kg/m2). Pathological diagnoses ranged from serous cystic neoplasm (32.5%), solid pseudopapillary neoplasm (22.2%), pancreatic neuroendocrine tumor (20.1%), intraductal papillary mucinous neoplasm (18.0%) to mucinous cystic neoplasm (5.2%). All patients had soft pancreatic texture. Main pancreatic duct diameters were ≤0.3cm for 158 patients (81.4%) and were ≥0.5cm in only 12 patients (6.2%). A stapler (57.7%) or hand-sewn closure (42.3%) were used to close the pancreatic remnant. The pancreatic anastomosis techniques used were duct to mucosa pancreaticojejunostomy (PJ)-interrupted suture (47.4%), duct to mucosa PJ-continuous suture (43.3%), duct to mucosa “HO” half-purse binding PJ (5.2%) and invaginating pancreaticogastrostomy (4.1%). Post-surgical incidences of CR-POPF of 45.9%, surgical site infection of 28.9%, postpancreatectomy hemorrhage of 7.7% and delayed gastric emptying of 2.1% were found. Obesity and pancreatic anastomosis technique were independent risk factors of CR-POPF, with a concordance index of 0.675 and an Area Under the Curve of 0.678. Discussion This novel nomogram constructed according to obesity and pancreatic anastomosis technique showed moderate predictive performance of CR-POPF after open CP.